2013
DOI: 10.3897/zookeys.257.4133
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of the genus Troglophilus (Rhaphidophoridae, Orthoptera) in Turkey: mitochondrial 16s rDNA evidences

Abstract: This study focuses on the evolutionary relationships among Turkish species of the cave cricket genus Troglophilus.Fifteen populations were studied for sequence variation in a fragment (543 base pairs) of the mitochondrial DNA (mtDNA) 16S rDNA gene (16S) to reconstruct their phylogenetic relationships and biogeographic history. Genetic data retrieved three main clades and at least three divergent lineages that could not be attributed to any of the taxa known for the area. Molecular time estimates suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Cave crickets, with a poor dispersal ability and broad distribution worldwide, are an ideal model to explain the roles of different palaeogeographic events in determining the current geographical distribution of different species (Weckstein et al, 2016;Allegrucci et al, 2017;Luo & Li, 2017). However, studies on cave crickets have mainly focused on the subfamilies Dolichopodainae and Troglophilinae in Europe (Allegrucci et al, 2005;Allegrucci et al, 2009;Ketmaier et al, 2009;Martinsen et al, 2009;Allegrucci et al, 2011;Kaya et al, 2013;Taylan et al, 2013;Taylan & Şirin, 2016;Allegrucci et al, 2017;Allegrucci & Sbordoni, 2019;Allegrucci et al, 2021), Macropathinae in Australia and New Zealand (Trewick, 2000;Goldberg et al, 2008;Cook et al, 2010;Beasley-Hall et al, 2018), as well as Ceuthophilinae in North America (Weckstein et al, 2016). A combination of dispersal and vicariance events are considered the main factors that have led to the current distribution pattern of species in Europe (Allegrucci et al, 2011;Allegrucci et al, 2017;Allegrucci & Sbordoni, 2019); while dispersal rather than vicariance was suggested as the likely explanation for the origin of the Chatham Islands biota in New Zealand (Trewick, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cave crickets, with a poor dispersal ability and broad distribution worldwide, are an ideal model to explain the roles of different palaeogeographic events in determining the current geographical distribution of different species (Weckstein et al, 2016;Allegrucci et al, 2017;Luo & Li, 2017). However, studies on cave crickets have mainly focused on the subfamilies Dolichopodainae and Troglophilinae in Europe (Allegrucci et al, 2005;Allegrucci et al, 2009;Ketmaier et al, 2009;Martinsen et al, 2009;Allegrucci et al, 2011;Kaya et al, 2013;Taylan et al, 2013;Taylan & Şirin, 2016;Allegrucci et al, 2017;Allegrucci & Sbordoni, 2019;Allegrucci et al, 2021), Macropathinae in Australia and New Zealand (Trewick, 2000;Goldberg et al, 2008;Cook et al, 2010;Beasley-Hall et al, 2018), as well as Ceuthophilinae in North America (Weckstein et al, 2016). A combination of dispersal and vicariance events are considered the main factors that have led to the current distribution pattern of species in Europe (Allegrucci et al, 2011;Allegrucci et al, 2017;Allegrucci & Sbordoni, 2019); while dispersal rather than vicariance was suggested as the likely explanation for the origin of the Chatham Islands biota in New Zealand (Trewick, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Object of this study are the species of genus Troglophilus belonging to the subfamily Troglophilinae Krauss, 1879, distributed from the eastern Alps to the Anatolian Peninsula (Eades, Otte, Cigliano, & Braun, ). Up to now, 21 species of Troglophilus have been described (Di Russo, Rampini, & Cobolli, ; Di Russo, Rampini, & Landeck, ; Karaman et al., ; Rampini & Di Russo, ,b; Taylan, Di Russo, Cobolli, & Rampini, ; Taylan, Di Russo, Rampini, & Cobolli, ; Taylan, Di Russo, Rampini, & Ketmaier, ; Taylan, Mol, & Sirin, ), with species diversity peaking along the Balkan Peninsula and in Anatolia (Turkey). Hence, differently from Dolichopoda that shows the highest diversity in peninsular and insular Greece, Troglophilus shows two separated centers of species richness with ten and six species described for Anatolia and Balkans, respectively.…”
Section: Introductionmentioning
confidence: 99%